'Not (yet) ready for the mainstream' - newly arrived migrant students in a separate educational program - Bunar, Nihad; Juvonen, Päivi (Journal of education policy, 2022)
The aim of this article is to describe and analyze how school leaders as key actors in policy enactment understand, talk about and act in relation to Newly Arrived Migrant Students (NAMSs) enrolled in a separate Language Introduction Program in Sweden. Drawing on the work of Stephen J. Ball and colleagues, we argue that a particular discursive formation of NAMSs, operating within constrains of various contextual factors, has a decisive impact on how policy as text is interpreted and enacted. Discursively formulating NAMSs as having multiple challenges, beyond Swedish language and insufficient grades, introduces various barriers. Policy flexibility in combination with power disparities thus allows school leaders, framed within legitimacy of 'rational explanations' and 'affirmative intentions', to negotiate policy meanings which are not always working in the students' best interests. Our empirically grounded and theoretically informed discussions showcase why there can be no inclusive education if NAMSs, during a protracted period, are physically, pedagogically and socially separated from mainstream structures. Consequently, and with the support in international research, we call for the overhaul of organizational approaches that allocate Newly Arrived Migrant Students to separate educational forms.